Design anthropological approaches in collaborative museum curation. (July 2021) - Stuedahl, Dagny; Lefkaditou, Ageliki; Ellefsen, Gro Synnøve; Skåtun, Torhild
Abstract : Museums show an increasing interest in participatory activities that open their premises and processes to diverse audiences. Inspired by this turn within museums, the exhibition FOLK adopted a multi-level co-design approach to address scientific racism and its heritage in contemporary science and society. Here we focus on the processes of collaborative curation during a series of public, pre-exhibition events and use the concepts of "knowledge pieces", "transformation" and "correspondence" to analyse how the events became curatorially consequential. We argue that the events acted as sensitising devices for the exhibition team by bringing together ethnographic and critical design methods. Highlights: Museum events facilitate for novel ways of thinking about collaborative processes and participation. Museum events may be akin to ethnographic fieldwork and sensitizing devices. Design anthropology supports collaborative curation with analytical concepts that refine empirical knowledge. Curatorial processes take the form of relational dialogues when negotiating matters of concern.